2017
DOI: 10.1186/s40168-017-0332-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy weight, gestational weight gain, and the gut microbiota of mothers and their infants

Abstract: BackgroundRecent evidence supports that the maternal gut microbiota impacts the initial infant gut microbiota. Since the gut microbiota may play a causal role in the development of obesity, it is important to understand how pre-pregnancy weight and gestational weight gain (GWG) impact the gut microbiota of mothers at the time of delivery and their infants in early life. In this study, we performed 16S rRNA gene sequencing on gut microbiota samples from 169 women 4 days after delivery and from the 844 samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
134
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 50 publications
(62 reference statements)
15
134
3
3
Order By: Relevance
“…The differences between previous studies and the present study might be due to different ethnicities and dietary habits of the study populations. Although pregestational weight, BMI and gestational weight gain reportedly correlate with microbiota composition during pregnancy, we did not detect any correlation of microbiota composition with these variables. The participants showed relatively small pregestational BMI values, which might contribute to the differences between previous reports and the present results.…”
Section: Discussioncontrasting
confidence: 95%
“…The differences between previous studies and the present study might be due to different ethnicities and dietary habits of the study populations. Although pregestational weight, BMI and gestational weight gain reportedly correlate with microbiota composition during pregnancy, we did not detect any correlation of microbiota composition with these variables. The participants showed relatively small pregestational BMI values, which might contribute to the differences between previous reports and the present results.…”
Section: Discussioncontrasting
confidence: 95%
“…Numerous factors are known to affect the diversity and architecture of the infant's gut microbiome during the first year of life, such as maternal factors (e.g. Body Mass Index and weight fluctuation) before pregnancy [11], gestational exposures [12][13][14][15] (e.g. maternal lifestyle, weight gain, pathophysiology conditions, supplements use, antibiotics exposure, pollutants exposure), mode of delivery [16,17] and type of feeding [18], triggering a gut microbiome dysbiosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive weight gain during pregnancy is known to be one of the maternal factors affecting the gut microbial composition of the newborn to delivery to adulthood [11] and previous human studies showed that children born to women who were affected by obesity or overweight during pregnancy exhibited significant variations in gut microbiome composition at the different stages of life, when compared with those from normal-weight mothers [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing consensus that maternal GM may have long‐term health consequences for the child (Stanislawski et al, ). It is therefore reasonable to suggest that vertically transmitted GM may act as a mechanism for intergenerational predisposition to psychological disorders.…”
Section: Gm Through the Lens Of A Case Formulation Frameworkmentioning
confidence: 99%
“…There is a growing consensus that maternal GM may have longterm health consequences for the child (Stanislawski et al, 2017).…”
Section: Vertical Transmissionmentioning
confidence: 99%